EU fta Negotiations with sadc and Mercosur: integration into the world economy or market access for EU firms? - Robles, AlfredoC (Third World Quarterly, 2008)
The EU claims that its free trade agreements with regional organisations of developing countries can promote the respective regions' integration into the world economy. Taking as case studies EU negotiations with the Southern African Development Community and Mercosur, the paper argues that the EU and its partners have different conceptions of integration into the world economy. For the EU the latter simply means multilateral trade liberalisation under the wto, while, for its partners, it involves increasing industrial production and exports of manufactured products. If the latter notion is accepted, an fta with the EU should increase European foreign direct investment into the region or at least increase their trade surpluses, thus increasing the resources available for support of local firms. The paper argues that an fta with the EU will not be likely to produce these results; thus the fta will simply be an instrument to promote market access for EU firms.